2010
DOI: 10.1099/ijs.0.013490-0
|View full text |Cite
|
Sign up to set email alerts
|

Ruegeria pelagia is a later heterotypic synonym of Ruegeria mobilis

Abstract: The 16S rRNA genes of Ruegeria pelagia NBRC 102038 T and Ruegeria mobilis NBRC 101030 T were resequenced and the results confirmed that they differ by only one base in their almost fulllength sequences (1425 nt). The gyrB gene sequence similarity between the two strains was also high (97.7 %). The outcome of API 20NE, API ZYM and antibiotic susceptibility tests showed that the two strains show only one difference, in b-galactosidase activity, in API tests and five differences in susceptibility among 30 tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Initial phylogenetic analysis by alignment of 16S rRNA gene sequences demonstrated that the strains were very homogenous and grouped in two very closely related clusters (99% identity) (Supplementary Figure S4). The two R. mobilis clusters included the type strain of R. mobilis NBRC101030 (and the synonymous R. pelagia NBRC102038 (Lai et al, 2010)), the R. mobilis strains isolated from Danish and Spanish turbot farms, and was distinct from other Ruegeria and Roseobacter clade species. Ruegeria (formerly Silicibacter) TM1040 was closely related to the main cluster (98%), but did cluster separately from our R. mobilis strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial phylogenetic analysis by alignment of 16S rRNA gene sequences demonstrated that the strains were very homogenous and grouped in two very closely related clusters (99% identity) (Supplementary Figure S4). The two R. mobilis clusters included the type strain of R. mobilis NBRC101030 (and the synonymous R. pelagia NBRC102038 (Lai et al, 2010)), the R. mobilis strains isolated from Danish and Spanish turbot farms, and was distinct from other Ruegeria and Roseobacter clade species. Ruegeria (formerly Silicibacter) TM1040 was closely related to the main cluster (98%), but did cluster separately from our R. mobilis strains.…”
Section: Resultsmentioning
confidence: 99%
“…Culture collection strains were R. mobilis NBRC101030 T and R. mobilis (formerly R. pelagia) NBRC102038 T . We earlier reported that R. mobilis and R. pelagia could not be distinguished based on 16S rRNA gene homology (Porsby et al, 2008) and R. pelagia is a later synonym of R. mobilis (Lai et al, 2010). For comparative purposes, we included a broader range of Roseobacter-clade bacteria, including several TDA producers (P. inhibens strains DSM17395 and 2.10, Ruegeria (Silicibacter) sp.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Silicibacter lacuscaerulensis (Petursdottir & Kristjansson, 1997) and Silicibacter pomeroyi (González et al, 2003) were transferred to the genus Ruegeria as two different species (Yi et al, 2007), and five more Ruegeria species, Ruegeria mobilis (Muramatsu et al, 2007), Ruegeria pelagia (Lee et al, 2007), Ruegeria scottomollicae (Vandecandelaere et al, 2008), Ruegeria marina (Huo et al, 2011) and Ruegeria faecimaris (Oh et al, 2011), have been described. However, it was recently shown that Ruegeria pelagia is a later synonym of Ruegeria mobilis (Lai et al, 2010). At the time of writing, the genus Ruegeria thus comprised seven recognized species.…”
mentioning
confidence: 99%
“…Ruegeria gelatinovorans and Ruegeria algicola have been reclassified as Thalassobius gelatinovorus (Arahal et al, 2005) and Marinovum algicola (Martens et al, 2006), respectively, and two species of the genus Silicibacter, Silicibacter lacuscaerulensis and Silicibacter pomeroyi, have been transferred to the genus Ruegeria (Yi et al, 2007). R. pelagia has been reported as a later heterotypic synonym of R. mobilis (Lai et al, 2010). All species of the genus Ruegeria have been isolated from marine environments with the exception of R. lacuscaerulensis, which was isolated from a geothermal lake (Petursdottir & Kristjansson, 1997).…”
mentioning
confidence: 99%